Novel Strategy Toward Light Absorption Enhancement of Organic Solar Cells Using M13 Bacteriophage - Jun, Minju; Nguyen, Thanh Mien; Kim, Sung Jo; Kim, Na Yeong; Lee, Ah Young; Kim, Jong H.; Oh, Jin Woo; Seo, Ji Youn (Solar RRL, 2023)
In organic photovoltaics (OPVs), the development of efficient light-harvesting organic donor and acceptor materials and the design of a device structure with appropriate visible light transmittance play an important role in increasing their power conversion efficiency. Light manipulation strategies in OPV are widely used to improve photovoltaic performance. One of the most popular technologies is antireflective coating (ARC), which enhances light utilization in devices. However, ARC has been investigated less in OPV cells than in organic silicon solar cells. Herein, a novel approach that employs the natural biomaterial M13 bacteriophage (M13) as an intermediate layer with a thickness of a few nanometers between the hole transport layer (HTL) and indium tin oxide is investigated. The functional surface hydrophilicity, obtained by genetic manipulation of M13, improves the light transmittance by more than 84% over the visible wavelength range of the OPV cells. Furthermore, it enhances the coherence between the HTL and the photoactive layer. Therefore, the photocurrent density and power conversion efficiency significantly increase, producing a high photovoltaic performance. The proposed approach of using natural biomaterials is the basis for a novel, low-cost, and eco-friendly design for light manipulation in solar cells.
Keywords: Anti reflective coatings; Hole transport layers; Light manipulation; M13 bacteriophage; Natural biomaterials; Novel strategies; Organic photovoltaic cell (OPVs); Organic photovoltaics; Photovoltaic performance; Power conversion efficiencies; light manipulation; M13 bacteriophage; organic photovoltaics; photocurrent; power conversion efficiency